STUDI EPIDEMIOLOGI DESKRIPTIF KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS LANGENSARI II KOTA BANJAR JAWA BARAT TAHUN 2017 - Solihati, Euis Novi; Suhartono, Suhartono; Winarni, Sri (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Pneumonia was one of leading under-five child mortality causes in Indonesia. Prevalence of cases at 2014 in Banjar City was included in the top ten (7,25%) in West Java. Banjar Public Health Office data showed the highest prevalence (2016) found in Langensari II Public Health Center (13,05%). This research aimed to describe epidemiology of pneumonia at under-five years according to characteristic of person, place, and time and mapping the spread of cases used spatial approach in Langensari II public health center working area from January 2016 until February 2017. Research type was descriptive observasional with crossectional design and spatial approach used GIS (Geographic Information System). 71 samples of children aged 0-59 months were taken by stratified random sampling and cases distribution mapping used total population. Dependent variable was pneumonia incidence, independent variables were individual characteristics, place characteristics (house physical condition and land use), and time. The results showed that the majority of cased were age 12-35 months (57%), male (57%), immunization history, breast milk and vitamin A were completed (81,7%;87,3%;87,3%), good nutrition status (71,8%), hadn’t low-birth weight history (93%), mother was graduation from junior high school (52,1%), unemployed mother (74,6%), temperature, humidity, natural light intensity, and cooking fuel type were ineligible (84,5%;69%;66,2%;53,5%), ventilation, floor type, and wall type were eligible (59,2%;63,4%;73,2%), smokers presence in family (76,1%), and not densely occupied (59,2%). The highest case was Langensari village with spreading points gathered in residential area. Langensari II public health care expected to hold socialization about pneumonia and simple healthy house to mother who have under-five child.